1993
DOI: 10.1128/iai.61.7.2966-2972.1993
|View full text |Cite
|
Sign up to set email alerts
|

Effects of strain variation, serotype, and structural modification on kinetics for activation and binding of C3 to Cryptococcus neoformans

Abstract: Incubation of encapsulated cells of Cryptococcus neoformans in normal human serum leads to activation of the alternative complement pathway and deposition of opsonic fragments of C3 into the capsule. We determined whether the variation in capsular structure that occurs among the four major cryptococcal serotypes was reflected in the kinetics for activation and binding of C3. We also examined the effects on activation kinetics of de-O-acetylation or periodate oxidation of the capsule. Binding kinetics were char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 26 publications
3
39
1
Order By: Relevance
“…Since the active C3 thioester group at the initiation of ACP has been shown to bind efficiently to mannose (19), it is reasonable that de-O-acetylation of CPS caused an increase in the capacity of CPS to activate ACP. In contrast with our observations, it has been reported that removal of O-acetyl substitution of the mannose backbone has a significant but relatively minor effect on the activation and binding of C3 to whole cells of C. neoformans (27,32). The discrepancy may be due to the form of activator used, soluble CPS or whole cells.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Since the active C3 thioester group at the initiation of ACP has been shown to bind efficiently to mannose (19), it is reasonable that de-O-acetylation of CPS caused an increase in the capacity of CPS to activate ACP. In contrast with our observations, it has been reported that removal of O-acetyl substitution of the mannose backbone has a significant but relatively minor effect on the activation and binding of C3 to whole cells of C. neoformans (27,32). The discrepancy may be due to the form of activator used, soluble CPS or whole cells.…”
Section: Discussioncontrasting
confidence: 99%
“…In recent comprehensive studies, Kozel and coworkers showed that encapsulated strains of C. neoformans are powerful activators of the complement system (18,32), and the activation and binding of C3 fragments to encapsulated cryptococci are due solely to the action of the ACP (17,31). On the other hand, Laxalt and Kozel (20) and Diamond and Erickson (3) previously reported that purified capsular polysaccharide was unable to activate ACP.…”
Section: Discussionmentioning
confidence: 99%
“…107 Fortunately, the capsule represents an extremely powerful activator of the complement cascade, achieving a deposition of up to 10 7 -10 8 C3 molecules per yeast cell while acapsular cryptococcal cells bind at least ten times less C3. [108][109][110] The predominant pathway as well as the precise localisation of opsonising C3 is species-specific; human complement induces a deposition of C3 at the outermost capsular surface, mainly via activation of the alternative pathway. 111 The localisation of C3 is of major importance for the efficacy of phagocytosis: whereas deposition inside the capsule is characteristic for poor phagocytosis, an opsonisation at the outer capsule edge allows efficient ingestion.…”
Section: Complement-mediated Effector Mechanisms In Cryptococcal Infementioning
confidence: 99%
“…In vitro, various GXM produce various effects in terms of antiphagocytic activity (Small and Mitchell, 1989) or induction of cytokine synthesis by different host cells (Chaka et al, 1997;Lipovsky et al, 1998). Finally, capsule structure seems to affect the in vitro binding of C3 to C. neoformans cells (Washburn et al, 1991;Young and Kozel, 1993). However, how the capsule influences yeast virulence is unknown.…”
Section: Introductionmentioning
confidence: 99%